An Urban Design Engineering Management Model Based on Data Analysis and Landscape Urbanism. (30th June 2022) - Li, Jingliang; Zhang, Wei; Wang, Xiaoxiao
Abstract : The error brought by space syntax in modeling computation and auxiliary analysis decision-making process has not been fully studied. In response to this phenomenon, this paper introduces two typical examples of digital visualization, 2D and 3D maps obtained using GIS and computer-aided design techniques, to design a multiflow system with elements interacting. By looking at flow models represented by traffic and walking, we consider how new real-time social media can be used to represent small-scale interactions at the spatial and social network levels. Watch how real-time data is sent to designers through various forms of dashboard by choosing the optimal radius, moderate model expansion range, with the aid of multisource urban data, choosing the appropriate fineness and modeling software.